2012
DOI: 10.1021/jp3064257
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced Photoluminescence and Photocatalytic Activities of Visible-Light-Responsive ZnS-AgInS2 Solid Solution Nanoparticles

Abstract: Semiconductor-metal nanocomposite materials composed of ZnS-AgInS2 solid solution (ZAIS) nanoparticles and SiO2-coated Au particles were prepared, the particle distance between ZAIS and Au being precisely adjusted in nanometer scale by changing the thickness of the SiO2 coating layer on Au core particles. The SiO2 layer also acted as an insulator layer to prevent direct electron transfer from photoexcited ZAIS to Au particles. The photoluminescent (PL) and photocatalytic properties of ZAIS particles were modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 45 publications
1
38
2
Order By: Relevance
“…Takahashi et al also observed the fluorescence intensity being predominantly quenched at low separations of dye and metal nanostructure. For 15 nm Au NPs they observed maximum SEF at a SiO2 thickness of d=21nm, and by using lifetime measurements it was confirmed that the enhancement was due to coupling to the electromagnetic field created by the excitation of the LSPR [31]. Ge et al used 30 nm Au NPs and observed maximum SEF at d=40nm.…”
Section: Papermentioning
confidence: 97%
“…Takahashi et al also observed the fluorescence intensity being predominantly quenched at low separations of dye and metal nanostructure. For 15 nm Au NPs they observed maximum SEF at a SiO2 thickness of d=21nm, and by using lifetime measurements it was confirmed that the enhancement was due to coupling to the electromagnetic field created by the excitation of the LSPR [31]. Ge et al used 30 nm Au NPs and observed maximum SEF at d=40nm.…”
Section: Papermentioning
confidence: 97%
“…For example, Tadjarodi et al have discovered that energy conversion efficiency of AgInS 2 nanoparticles is 1.58% when fill factor is 30%, which revealed the capability of AgInS 2 nanoparticles to be used in solar cell devices [16]; Luo et al have synthesized water-soluble AgInS 2 (AIS) nanocrystals (NCs) and ZnS-AgInS 2 (ZAIS) NCs, and found that AIS and ZAIS NCs showed promising photocatalytic activities in the degradation of rhodamine B [17]. Takahashi et al have investigated the photocatalytic activity of ZnS-AgInS 2 solid solution nanoparticles for H 2 evolution [18].…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] It was also reported that the photocatalytic activity and photostability of graphene-based solid-solution sulfide composites are usually much higher than those of graphene-based monometal sulfide composites. [31,32] For example, Zhang et al prepared a graphene-Zn x Cd 1Àx S nanocomposite by a coprecipitation-hydrothermal method with Na 2 S as the inorganic S source, and the obtained graphene-Zn 0.8 Cd 0.2 S product exhibited significantly improved photocatalytic H 2 -production activity compared to pristine Zn 0.8 Cd 0.2 S, and even better activity than optimized Pt-Zn 0.8 Cd 0.2 S under the same reaction conditions. [32] However, the effects of different S sources on the formation of high-quality composites between graphene and Zn x Cd 1Àx S solid solutions remains unexplored.…”
Section: Introductionmentioning
confidence: 99%